2020
DOI: 10.7710/2168-0620.0293
|View full text |Cite
|
Sign up to set email alerts
|

Weathering the Storms: Workplace Wellbeing, Mental Health, and the U.S. Meteorologist

Abstract: Mental health is a topic of increasing interest and concern across the weather enterprise amidst a backdrop of funding cuts, extreme storms, and longer, more involved work hours. The present study therefore investigated wellbeing in the meteorological workplace. Participants (N= 389), professional meteorologists (n = 360) and professionally-employed meteorology students (n = 29), voluntarily participated in a Qualtrics-hosted online survey and responded to a number of measures representing a broad range of men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 49 publications
1
7
1
Order By: Relevance
“…programming, and more-scored highest in impostor syndrome as well as downward social comparison. This contrasts their higher job satisfaction ratings found by Bolton and Ault (2020),…”
Section: Correlational Analysescontrasting
confidence: 83%
See 2 more Smart Citations
“…programming, and more-scored highest in impostor syndrome as well as downward social comparison. This contrasts their higher job satisfaction ratings found by Bolton and Ault (2020),…”
Section: Correlational Analysescontrasting
confidence: 83%
“…Wood et al (2008) found no relation between social desirability and authenticity, Pearson r bivariate correlational analysis in this study indicated socially-desirable responding for the authentic living subscale specifically, r(196) = 0.17, p = 0.02, suggesting a majority of our participants tried to manipulate their self-presentation as more authentic. Considering this noteworthy due to Bolton and Ault's (2020) findings on image management in another sample of meteorologists, with respect to aspects of burnout and happiness-were meteorologists attempting to manage our impressions of them here, too?-we split the sample by group and found that the meteorologists did not contribute to this relationship, with r(82) = .08, p = .449. Our data instead suggests that the general population (r[101] = .24, p = .02) carried this association.…”
Section: Survey Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…ourselves or anyone else. " -Fred Rogers (1928-2003 Meteorologists are increasingly concerned with mental health, as evidenced by discussions in publications (Bolton, Ault, Greenberg, & Baron-Cohen, 2018;Bolton & Ault, 2020;Bolton & DePodwin, 2019;Gilford, Moser, DePodwin, Moulton, & Watson, 2019), presentations at weather and other conferences, and in postings on social media. However, discourse has been primarily anecdotal, while psychological concepts related to trauma have been only loosely-defined.…”
Section: "Some Days Doing 'The Best We Can' May Still Fall Short Of What We Would Like To Be Able To Do But Life Isn't Perfect-on Any Fromentioning
confidence: 99%
“…Although meteorologists appear psychologically stable in a relative sense (Bolton et al, 2018;Bolton & Ault, 2020), recent and ongoing discussion within the weather enterprise shows they are not immune to these processes, which are separate from more generalized professional workplace burnout (Newell & MacNeil, 2010). That being said, all of this discussion, which might be rather abstract, begs the question of how one can cope with difficult emotions.…”
Section: Emotional Processing In the Meteorological Workplacementioning
confidence: 99%